Pengaruh Pemberian Puree Daun Kelor (Moringa oleifera) Terhadap Sifat Kimia Dan Organoleptik Nugget Ikan Cakalang (Katsuwonus pelamis) - Pattikawa, Stevani O; Mailoa, Meitycofrida; Augustyn, Gelora H (Jurnal Agrosilvopasture-Tech, 2023)
The purpose of this study was to determine the chemical and organoleptic characteristics of fish nuggets with the addition of Moringa puree. This study was designed using a one-factor Completely Randomized Design, namely the concentration of Moringa leaf puree with four treatment levels 0%, 20%, 40% and 60% with two replications. Variables observed included moisture content, ash content, fat content, protein content and carbohydrate content as well as hedonic tests and hedonic quality of color, taste, aroma and texture. The results showed that there was a change in the chemical and organoleptic properties of fish nuggets. The water content decreased, while the ash, fat, protein and carbohydrate content increased with the addition of the concentration of Moringa puree from the beginning of the treatment. As well as influencing the hedonic assessment and hedonic quality of the panelists.